2010
DOI: 10.1111/j.1365-2966.2010.17879.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the nearby long, soft GRB 100316D with an associated supernova

Abstract: We report the Swift discovery of the nearby long, soft gamma-ray burst GRB 100316D, and the subsequent unveiling of its low-redshift host galaxy and associated supernova. We derive the redshift of the event to be z = 0.0591 ± 0.0001 and provide accurate astrometry for the gamma-ray burst (GRB) supernova (SN). We study the extremely unusual prompt emission with time-resolved γ -ray to X-ray spectroscopy and find that the spectrum is best modelled with a thermal component in addition to a synchrotron emission co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
221
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(246 citation statements)
references
References 81 publications
23
221
0
2
Order By: Relevance
“…The Swift-identified low luminosity events to date -GRB 060218 (Campana et al 2006) and GRB 100316D (Starling et al 2011) -appear to be of extremely long duration (2000 s in the case of GRB 060218) with extremely smooth light curves. They are also very soft events in which the Xray emission exceeds that in the γ−ray (so called X-ray Flashes).…”
Section: Burst Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Swift-identified low luminosity events to date -GRB 060218 (Campana et al 2006) and GRB 100316D (Starling et al 2011) -appear to be of extremely long duration (2000 s in the case of GRB 060218) with extremely smooth light curves. They are also very soft events in which the Xray emission exceeds that in the γ−ray (so called X-ray Flashes).…”
Section: Burst Propertiesmentioning
confidence: 99%
“…Only a handful of such low luminosity events have been identified in the past decade, all of which have been relatively local (given the difficulty in observing low luminosity bursts beyond z ∼ 0.1). These include the well studied GRBsupernova pairs GRB 980425/SN 1998bw (Galama et al 1998), GRB 031203/SN 2003lw (Malesani et al 2004;Soderberg et al 2004), GRB 060218/SN 2006aj (Pian et al 2006) and GRB 100316D/SN 2010bh (Starling et al 2011;Cano et al 2011), and the enigmatic GRBs 060505 and 060614, where associated SNe have been ruled out to deep limits, and whose origin remains mysterious (Fynbo et al 2006;Della Valle et al 2006). They may be low luminosity events akin to those above, but where the SNe is absent (e.g.…”
Section: Burst Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of an additional blackbody component in the prompt X-ray spectrum of GRB 060218 (Campana et al 2006) and GRB 100316D (Starling et al 2011) has been reported. The blackbody temperature is stable in the range of 0.1-0.2 keV up to several hundreds of seconds after the trigger, and then, decreases to < 0.01 keV.…”
Section: Additional Blackbody Component In X-ray Spectrummentioning
confidence: 99%
“…While GRB 060218 and GRB 100316D show a duration of several thousands of seconds (Campana et al 2006;Starling et al 2011), SN-GRBs with a duration of a several tens to hundreds of seconds are also common. Although the durations of GRB 060218 and GRB 100316D are exceptionally long, the rest of the sample is well within the duration distribution of typical long GRBs (Figure 2).…”
Section: Durationsmentioning
confidence: 99%